Online Task-Based Language Learning to Enhance Thai Monks’ Speaking Performance - Dawilai, Sirikanya; Santhi, Natthaphon; Wetpichetkosol, Bhudthree (Journal of Mobile Multimedia, 2024)
This research aimed to achieve two main objectives: (1) to assess the learning achievements in online task-based language learning, and (2) to evaluate satisfaction with the utilization of the online task-based language learning model. The study’s population comprised Buddhist monk students from four provinces in Thailand: Chiang Rai, Phrae, Phayao, and Nan. A total of 80 participants took part in a 30-hour English language training program that focused on task-based language teaching (TBLT) implemented through online technology to enhance Thai monks’ speaking performance. Zoom and free online tools such as Pronunciation Checker App were integrated into the TBL learning cycle to deliver this online training. The research process can be summarized four stages consisting of orientation stage, pre-practicing stage, practicing stage, and post-practicing stage. The comparison of learning outcomes before and after the implementation of the instructional model for monks revealed a significant difference in the average scores. The overall score before training was 38.78 (S.D. = 5.85), while the post-training learning outcomes had a higher average score of 47.34 (S.D. = 4.99). The assessment of satisfaction was divided into four dimensions: (1) content and language usage; (2) English instructional activities for monks; (3) teaching and learning process; and (4) development of English-speaking skills. Overall, participants expressed high levels of satisfaction across all four dimensions of the instructional design approach, with a mean rating of 4.49 and a standard deviation of 0.56.